A review of radiological definitions of sarcopenia in cancer. Issue 2 (2nd March 2023) - Wang, James W.; Chen, Jiarong; McGregor, Alison H.; Williams, Matthew
Abstract: Background: Sarcopenia in cancer impacts overall survival, surgical complications, and side effects of oncological treatments. Cancer patients frequently receive cross‐sectional imaging, allowing incidental capture of radiological sarcopenia biomarkers. These biomarkers vary by imaging modality, tumour group, patient demographics, and anatomy but lack a consensus with regard to clinical application. In this article, we provide an overview of radiology‐based sarcopenia biomarkers by anatomy and their prevalence in the literature. Methods: In accordance with previously published scoping review protocol, we searched PubMed/MEDLINE, Embase, Scopus, and Cochrane between 2007 and June 2021. Studies were independently reviewed by two authors with Cohen's kappa 0.81 and reported using descriptive statistics. Results: There were 5649 titles and abstracts reviewed, including 459 full‐text articles. There were 23 additions found through references, resulting in 482 total studies. There is a consistent year‐on‐year increase of new radiological sarcopenia landmarks since 2015, with 49.8% studies reporting novel definitions of sarcopenia. The majority of studies ranged between 50 and 300 participants and featured an abdominal sarcopenia marker (94.4%), of which 75.2% used the skeletal muscle index at L3 (L3SMI). Sarcopenia prevalence ranged from 8.33% to 89.66%. Biomarkers are often applied across genders and ethnicities, regardless of the original population the definition originated from, despite the emergence and availability of ethnic‐specific alternatives. Conclusion: There remains a need to incorporate demographics and age into predictive models derived from sarcopenia biomarkers obtained through routine clinical imaging. Use of individual biomarkers needs to be made with careful consideration of the population in which the biomarkers were generated.